From gadgets towards community: communion ecclesiology and botho as tools for crossing the digital divides - Resane, K. Thomas (Stellenbosch theological journal, 2024)
South Africa is a divided racially, religiously, economically, politically and digitally country. Gadgets become personal and humans gravitate towards them instead of towards each other where botho can be experienced. Technology has negative and positive impacts on the community. This article provides some practical steps from theological perspective for citizens to cross the digital divides. It is here recommended that botho be interpreted through communion ecclesiology lenses. To do this communion ecclesiology and botho will be elaborated, compared, and contrasted. Through the literature review and social media, these two tools are presented as a solution towards divided communities of faith. The findings are that the digital divides can be overcome through theological reflections, self-offering, and robust engagement with communities. The contribution made by this article is that communality cannot be bought. Becoming a spiritual community comes through self-denial and crossing the digital divides - being incarnationally present on the cutting edges of communities.